2023
DOI: 10.1002/agj2.21315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage and nitrogen fertility on growth, yield, and seed chemical composition of rainfed Brassica carinata

Abstract: The combination of subsoil compaction and injudicious usage of nitrogenous fertilizers are key factors that may lower crop yields, especially in soils with a shallow hardpan. Therefore, the objective of this study was to determine the effects of tillage and N application on carinata productivity in rainfed conditions. A 3-year field study was conducted at the North Florida Research and Education Center, Quincy, FL, USA. Treatments were four rates of N (0, 45, 90, and 135 kg N ha −1 ) and three tillage methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…However, authors [31,35] reported a seed loss as high as 11% after swathing. Conversely, swathing is a common practice, for example in Canola harvesting in Canada to reduce natural pod shattering and protect the crop from untimely frost or hail [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, authors [31,35] reported a seed loss as high as 11% after swathing. Conversely, swathing is a common practice, for example in Canola harvesting in Canada to reduce natural pod shattering and protect the crop from untimely frost or hail [36].…”
Section: Introductionmentioning
confidence: 99%
“…This new crop would reflect the 100 years or so of intense breeding and selection for high yield and desirable agronomic traits that created the current commodity soybean cultivars. Many proposed new crops for oil and renewable diesel production (carinata, camelina, and pennycress; Keadle et al., 2023; Seepaul et al., 2023) have not benefited from extensive breeding, so it will take years before their yields will be competitive with soybean, even if molecular breeding techniques accelerate productivity improvement (Saeed et al., 2022).…”
mentioning
confidence: 99%
“…It will not require N fertilizer to produce maximum yield (Almeida et al., 2023), thereby avoiding the energy intensive production and pollution problems often associated with the use of N fertilizer (Gao & Serrenho, 2023). The new oil crops under consideration (canola, carinata, pennycress, and camelina) require N fertilizer to produce high yields (Glenn et al., 2021; Seepaul et al., 2023).…”
mentioning
confidence: 99%